Design And Build Monitoring System Temperature And Ph Hydroponic Plants Based On Internet Of Things (Iot) Technology Using Nodemcu Esp-8266 Microcontroller - Alfianur, Muhammad Fahri; Arbansyah, Arbansyah; Sumadi, Muhammad Taufiq (JSE Journal of Science and Engineering, 2025)
Hydroponic agriculture is a soilless plant cultivation method that is becoming increasingly popular in the modern era. However, hydroponic systems require strict monitoring of environmental parameters, especially temperature and pH, to ensure optimal plant growth. This research aims to design and build a temperature and pH monitoring system for hydroponic plants based on the Internet of Things (IoT) using a NodeMCU ESP-8266 microcontroller. The developed system consists of a DS18B20 temperature sensor, a pH sensor, a NodeMCU ESP-8266 microcontroller, and the ThingSpeak IoT platform. These sensors are used to measure the temperature and pH of the hydroponic nutrient solution in real-time. The collected data is then sent to the ThingSpeak platform via the WiFi connection integrated into the NodeMCU ESP-8266. The implementation of this system is expected to assist hydroponic farmers in efficiently monitoring and controlling their plants' environmental conditions, thereby increasing productivity and harvest quality. Further research can be conducted to integrate more parameters and develop automatic control systems based on the collected data.